Fire-retardant waterproof and breathable membrane for construction and fire-retardant method thereof
Patent Information
- Application Number
- CN202510731795.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-06-03
AI Technical Summary
[0007]本发明的目的在于提供一种用于建筑的阻燃型防水透气膜及其阻燃方法,以解决上述背景技术中提出的因湿气导致的墙面发霉、地板变形、木材腐蚀等的技术问题
1.本发明通过交替排列聚氨酯与聚偏氟乙烯-六氟丙烯共聚物纤维的互穿网络结构,保证驱动水蒸气通过,避免水滴渗透,协同实现透气膜的高透气率;
Smart Images

Figure CN120401127B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waterproof and breathable membrane technology, specifically to a flame-retardant waterproof and breathable membrane for building applications and its flame-retardant method. Background Technology
[0002] In areas with abundant rainfall and humid air, building materials exposed to moisture for extended periods are prone to water absorption, swelling, softening, and even rotting, leading to decreased structural strength and subsequent cracking and detachment. Secondly, the damp environment provides ideal conditions for mold growth, negatively impacting indoor air quality. Therefore, as people's demands for higher-quality living environments increase, the market demand for waterproof and breathable membranes continues to grow.
[0003] Waterproof and breathable membranes effectively block rainwater intrusion, keeping the interior dry while allowing water vapor to escape, preventing internal moisture buildup. Furthermore, the flame-retardant properties of these membranes provide additional safety in the event of a fire, slowing its spread.
[0004] Patent CN106827687B discloses an ultra-thin, highly flame-retardant, breathable, and waterproof membrane and its preparation method. The above patent achieves the protection of the functional layer, has good waterproof and breathable performance, good anti-aging performance, good extensibility, and the product is lightweight and thin, making it suitable for use in various environments.
[0005] The aforementioned patent has excellent flame retardant effect, solving the problems of existing waterproof and breathable membranes not having good flame retardant effect and being too thick. However, there is still room for optimization in terms of moisture permeability of waterproof and breathable membranes. This application achieves high air permeability of breathable membranes, solving problems such as mold growth on walls, deformation of floors, and corrosion of wood caused by moisture.
[0006] Therefore, this application proposes a flame-retardant waterproof breathable membrane for building applications that achieves high air permeability and a flame-retardant method thereof. Summary of the Invention
[0007] The purpose of this invention is to provide a flame-retardant, waterproof, and breathable membrane for building construction and a flame-retardant method thereof, so as to solve the technical problems mentioned in the background art, such as wall mold, floor deformation, and wood corrosion caused by moisture.
[0008] To achieve the above objectives, the present invention provides the following technical solution: a flame-retardant, waterproof, and breathable membrane for construction, comprising a microporous membrane, wherein the microporous membrane comprises the following components by weight: 40-60 parts of flame-retardant polyurethane, 5-15 parts of flame-retardant material, 20-30 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 0.4-2 parts of lithium chloride, and 1-5 parts of short-chain fluorinated polymer resin; the preparation method of the microporous membrane comprises the following steps: (1) Add flame-retardant polyurethane and half of lithium chloride to the solvent, heat and stir in a water bath at 60 °C for 4 h to obtain polyurethane spinning solution; (2) Pour the polyvinylidene fluoride-hexafluoropropylene copolymer, short-chain fluorinated polymer resin, flame retardant material and the remaining lithium chloride into a solvent and stir to obtain copolymer spinning solution; (3) The polyurethane spinning solution and the copolymer spinning solution are respectively loaded into the syringe of the multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution are arranged alternately. A voltage of 50kV and a feed speed of 3mL / h are applied to perform electrospinning to obtain a microporous membrane.
[0009] Preferably, nanofiber membranes are bonded to both sides of the microporous membrane, and the preparation method of the nanofiber membrane includes the following steps: Lithium chloride was added to a mixture of tetrahydrofuran and N,N-dimethylformamide, followed by the addition of aminestyrene-butadiene-styrene block copolymer and hydrogen-containing silicone oil. The mixture was stirred to obtain a mixed spinning solution. The mixed spinning solution is propelled through the syringe of a multi-needle electrospinning machine to spin nanofiber membranes.
[0010] Preferably, the nanofiber membrane is coated with a waterproof coating, and the method for preparing the waterproof coating includes the following steps: The epoxy silicone oil and isopropanol were poured into the reaction vessel in sequence and stirred. The silane coupling agent was added dropwise, followed by tetraethyl orthosilicate and octyltriethoxysilane. The mixture was stirred for 0.5 h. Add deionized water to obtain the preproduct. Blend the self-healing microcapsules with the preproduct to obtain the waterproof coating material.
[0011] Preferably, the method for preparing the flame-retardant material includes the following steps: The trichlorophosphazene dissolved in tetrahydrofuran was poured into a reaction flask containing potassium carbonate. 2,2'-biphenyl hydroquinone dissolved in tetrahydrofuran was added dropwise to the reaction flask. The mixture was reacted in an ice bath for 30 minutes. The mixture was then filtered and rotary evaporated to obtain the crystalline product. Tetrahydrofuran and hexamethylenediamine are added to a reaction vessel and stirred. The crystalline product dissolved in tetrahydrofuran is then added dropwise to the reaction vessel, followed by filtration, washing, and distillation to obtain a flame-retardant material.
[0012] Preferably, the flame-retardant polyurethane is a vanillin-based flame-retardant polyurethane, and the preparation method of the vanillin-based flame-retardant polyurethane includes the following steps: Hexamethylene diisocyanate and dibutyltin dilaurate were added to polytetrahydrofuran diol and heated to 70°C under a nitrogen atmosphere to obtain a polyurethane prepolymer. The vanillin-based flame retardant monomer was dissolved in N,N-dimethylacetamide to obtain a solution of the vanillin-based flame retardant monomer. The vanillin-based flame retardant monomer solution and chain extender 1,4-butanediol were added to the polyurethane prepolymer, and dibutyltin dilaurate was added dropwise to obtain the reactants. The reactants were poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 24 hours. The product in the mold was then placed in a vacuum drying oven and dried at 70°C for 24 hours to obtain vanillin-based flame-retardant polyurethane.
[0013] Preferably, the preparation method of the vanillin-based flame retardant monomer includes the following steps: Vanillin was dissolved in ethanol, heated to 60°C under a nitrogen atmosphere, and 4,4-diaminodiphenylmethane dissolved in ethanol was added dropwise. Then, flame retardant diphenyl phosphate was added to obtain a mixture. The mixture was poured into dichloromethane, recrystallized from ethanol, filtered and washed, and the washed product was placed in a vacuum drying oven and dried at 80°C for 24 hours to obtain vanillin-based flame retardant monomer.
[0014] Preferably, the method for preparing the self-healing microcapsules includes the following steps: Tetraethyl orthosilicate, anhydrous ethanol, and deionized water are mixed and stirred until homogeneous to obtain a silanol solution. Pour gum arabic powder into deionized water, add epoxy resin, monohydroxy polydimethylsiloxane and dimethyl methylphosphonate, and then proceed with emulsification to obtain an emulsion. A silanol solution was added dropwise to the emulsion, the pH was adjusted to 9 with ammonia, and the mixture was reacted in a water bath at 50 ℃ for 6 hours to obtain silica gel shell microcapsules. The silica gel shell microcapsules were poured into a copper chloride solution, tannic acid solution was added, and the mixture was reacted in a 50 °C water bath for 24 h. After filtration and washing, the self-healing microcapsules were obtained.
[0015] Preferably, the solvent is one of N,N-dimethylformamide and N,N-dimethylacetamide, and the microporous membrane and the nanofiber membrane are bonded together by hot pressing.
[0016] Preferably, the flame-retardant method includes the following steps: S1. When the waterproof and breathable membrane burns, the microporous membrane in the waterproof and breathable membrane forms a dense char layer, which acts as a flame retardant.
[0017] Preferably, the flame-retardant method further includes the following steps: When the S11 waterproof and breathable membrane is damaged by fire, the self-healing microcapsules rupture and release dimethyl methylphosphonate, forming a local flame-retardant barrier.
[0018] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention achieves high air permeability of the breathable membrane by alternating interpenetrating network structures of polyurethane and polyvinylidene fluoride-hexafluoropropylene copolymer fibers, ensuring the passage of water vapor and preventing water droplet penetration. 2. This invention enhances the waterproof performance of the breathable membrane by attaching nanofiber membranes to the upper and lower sides of the microporous membrane, making the nanoscale pores of the nanofiber membrane complementary to the microscale pores of the microporous membrane. The high flexibility and tear resistance of the nanofiber membrane also improve the overall mechanical properties of the breathable membrane. 3. This invention achieves superhydrophobicity of the coating by spraying a waterproof coating onto a nanofiber membrane, with octyl long-chain alkyl groups anchored to the coating surface through hydrolysis, forming a low surface energy structure and improving the waterproof performance of the breathable membrane. 4. This invention uses copolymer fibers to encapsulate flame-retardant materials. The terminal amino groups in the flame-retardant material form hydrogen bonds with the fluorocarbon groups in the polyvinylidene fluoride-hexafluoropropylene molecular chain in the microporous membrane, which enhances the interfacial bonding force between the char layer and the matrix, improves the stability of the char layer, and improves the flame-retardant performance of the breathable membrane. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the microporous membrane preparation process of the present invention; Figure 2 This is a schematic diagram of the nanofiber membrane preparation process of the present invention; Figure 3 This is a schematic diagram of the waterproof coating preparation process of the present invention; Figure 4 This is a schematic diagram of the flame-retardant material preparation process of the present invention; Figure 5 This is a schematic diagram of the flame-retardant polyurethane preparation process of the present invention; Figure 6 This is a schematic diagram of the preparation process of the vanillin-based flame retardant monomer of the present invention; Figure 7 This is a schematic diagram of the self-healing microcapsule preparation process of the present invention; Figure 8 This is a schematic diagram of the solvent of the present invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1, please refer to Figure 1 and Figure 8A flame-retardant, waterproof, and breathable membrane for building applications, the preparation method of which includes the following steps: 60 parts of flame-retardant polyurethane and 1 part of lithium chloride were added to a solvent and heated and stirred in a water bath at 60 °C for 4 hours to obtain a polyurethane spinning solution. 30 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 5 parts of short-chain fluorinated polymer resin, 15 parts of flame retardant material and 1 part of lithium chloride were poured into a solvent and stirred to obtain copolymer spinning solution. The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. Nanofiber membranes are bonded to the top and bottom sides of the microporous membrane, and then hot-pressed. A waterproof coating is then sprayed onto the nanofiber membrane to obtain a waterproof and breathable membrane.
[0022] Furthermore, by alternating the multi-needle arrangement of polyurethane and polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution, the two types of nanofibers form an interpenetrating network structure during deposition. The polyurethane fibers form coarser fibers, while the polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution forms finer fibers due to its high electrical conductivity. The interweaving of coarse and fine fibers creates multi-scale pores. The coarse fibers provide mechanical support, while the fine fibers increase the specific surface area, synergistically achieving high air permeability. During the spinning process, lithium chloride evaporates with the solvent, forming microphase separation and inducing nanoscale pores on the surfaces of the polyurethane and polyvinylidene fluoride-hexafluoropropylene fibers. At the same time, lithium chloride increases the electrical conductivity of the spinning solution, thereby enhancing the jet stretching degree, making the fiber diameter more uniform, and reducing closed-pore defects in the microporous membrane. Due to its high fluorine content, the polyvinylidene fluoride-hexafluoropropylene fiber forms a dense surface layer, which carbonizes at high temperatures during the combustion of the breathable membrane to generate a continuous barrier that isolates oxygen. Blending polyvinylidene fluoride (PVDF)-hexafluoropropylene (HCF) copolymers with short-chain fluorinated polymers creates a low surface energy structure on the surface of PVDF-HCF fibers, imparting superhydrophobicity to the microporous membrane and preventing liquid water from permeating the breathable membrane. Hydrophilic groups in the polyurethane fibers, such as urethane esters, form water molecule transport channels with lithium chloride residues, allowing water vapor to pass through. The microporous membrane formed by alternating spinning exhibits asymmetric wettability, with the polyurethane side being hydrophilic and the PVDF-HCF side hydrophobic, ensuring the passage of water vapor while preventing backflow of external moisture. Furthermore, the high elongation at break of the polyurethane fibers provides flexibility to the microporous membrane, while the high modulus of the PVDF-HCF fibers and the crystalline regions of the fluorinated resin enhance the tear resistance of the microporous membrane. The short-chain fluorinated resin, acting as a compatibilizer, strengthens the interfacial bonding between the polyurethane fibers and the PVDF-HCF fibers, thereby improving the mechanical properties of the breathable membrane.
[0023] Example 2, please refer to Figure 1and Figure 2 A flame-retardant, waterproof, and breathable membrane for building applications, the preparation method of which includes the following steps: 55 parts of flame-retardant polyurethane and 0.8 parts of lithium chloride were added to a solvent and heated and stirred in a water bath at 60 °C for 4 hours to obtain a polyurethane spinning solution. 28 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 4 parts of short-chain fluorinated polymer resin, 13 parts of flame retardant material and 0.8 parts of lithium chloride were poured into a solvent and stirred to obtain copolymer spinning solution. The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. Lithium chloride was added to a mixture of tetrahydrofuran and N,N-dimethylformamide, along with amine-styrene-butadiene-styrene block copolymer and hydrogen-containing silicone oil. The mixture was stirred to obtain a mixed spinning solution. The mixed spinning solution was propelled through the syringe of a multi-needle electrospinning machine to spin nanofiber membranes. Nanofiber membranes were then bonded to the top and bottom sides of the microporous membrane and subjected to hot pressing. A waterproof coating was then sprayed onto the nanofiber membranes to obtain a waterproof and breathable membrane.
[0024] Furthermore, the nanofiber membrane possesses an extremely high specific surface area and a dense nanoscale pore structure. When the nanofiber membrane is bonded to the surface of the microporous membrane, the nanoscale pores of the nanofiber membrane effectively block the penetration of tiny water droplets while not affecting the permeation of water vapor. This creates a complementary relationship between the nanoscale pores of the nanofiber membrane and the microscale pores of the microporous membrane, further enhancing the waterproof performance of the breathable membrane. The elastic properties of the amine-styrene-butadiene-styrene nanofibers, combined with the microporous membrane through hot-pressing, form a tortuous and interconnected breathable path, allowing for efficient water vapor transport. Liquid water is blocked due to surface tension, ensuring the waterproof and breathable properties of the breathable membrane. Simultaneously, the introduced hydrogen-containing silicone oil lowers the surface energy of the nanofiber membrane, giving it better hydrophobic properties and improving its water resistance. Furthermore, the Si-H bonds within the hydrogen-containing silicone oil are further enhanced through hot pressing. The process involves forming a low surface energy composite structure with the fluorinated resin in the microporous membrane, further improving the hydrophobicity of the breathable membrane. Aminostyrene-butadiene-styrene, as a thermoplastic elastomer, imparts high flexibility and tear resistance to the nanofiber membrane, forming a composite structure with the fibers in the microporous membrane, enhancing the overall bending resistance and impact resistance of the breathable membrane. During hot pressing, the styrene blocks in the nanofiber membrane physically entangle with the polyurethane in the microporous membrane. Simultaneously, the Si-H bonds in the hydrogen-containing silicone oil form hydrogen bonds with the urethane groups of the polyurethane, further enhancing the interlayer bonding strength and thus improving the overall mechanical properties of the breathable membrane. When the breathable membrane burns, the butadiene segments of the nanofiber membrane carbonize to form an expanded char layer, and the fluorinated resin in the microporous membrane decomposes at high temperature to generate a Si-OC ceramic layer. The two layers overlap to form a dense heat insulation barrier, thereby preventing the spread of fire.
[0025] Example 3, please refer to Figure 1 and Figure 3 A flame-retardant, waterproof, and breathable membrane for building applications, the preparation method of which includes the following steps: 50 parts of flame-retardant polyurethane and 0.6 parts of lithium chloride were added to a solvent and heated and stirred in a water bath at 60 °C for 4 hours to obtain a polyurethane spinning solution. 26 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 3 parts of short-chain fluorinated polymer resin, 10 parts of flame retardant material and 0.6 parts of lithium chloride were poured into a solvent and stirred to obtain copolymer spinning solution; The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. End-capsulated silicone oil and isopropanol were sequentially poured into a reaction vessel and stirred. A silane coupling agent was added dropwise, followed by tetraethyl orthosilicate and octyltriethoxysilane. The mixture was stirred for 0.5 hours, and then deionized water was added dropwise to obtain the preproduct. The self-healing microcapsules were blended with the preproduct to obtain a waterproof coating material. Nanofiber membranes were then bonded to the upper and lower sides of the microporous membrane and subjected to hot pressing. Finally, a waterproof coating was sprayed onto the nanofiber membrane to obtain a waterproof and breathable membrane.
[0026] Furthermore, the three-dimensional network structure of silica generated by the hydrolysis of tetraethyl orthosilicate chemically cross-links with the epoxy groups of the terminal epoxy silicone oil through a silane coupling agent, generating a dense coating material. Spraying this coating onto the surface of the nanofiber membrane further prevents liquid water from permeating the breathable membrane. The octyl long-chain alkyl groups are anchored to the coating surface through hydrolysis, forming a low surface energy structure that achieves superhydrophobicity, repelling liquid water while allowing water vapor to permeate. The silica particles formed by the hydrolysis of tetraethyl orthosilicate, together with the self-healing microcapsules, construct a multi-level porous structure. The interconnected ventilation channels ensure the permeability of water vapor. When the breathable membrane burns, the epoxy silicone oil in the coating decomposes upon heating to generate silica particles, which react with the hydrogen fluoride gas from the decomposition of polyvinylidene fluoride-hexafluoropropylene in the microporous membrane to generate SiF3· free radicals. These free radicals then capture the H· and OH· free radicals generated in the combustion chain reaction, thereby inhibiting the spread of fire. The silica skeleton formed by the coating overlaps with the carbon layer formed by polyvinylidene fluoride-hexafluoropropylene in the microporous membrane to form a ceramic barrier, which blocks heat and oxygen exchange and further improves the flame retardant performance of the breathable membrane.
[0027] Example 4, please refer to Figure 1 and Figure 4 A flame-retardant, waterproof, and breathable membrane for building applications, the preparation method of which includes the following steps: 45 parts of flame-retardant polyurethane and 0.4 parts of lithium chloride were added to a solvent and heated and stirred in a water bath at 60 °C for 4 hours to obtain a polyurethane spinning solution. Trichlorophosphazene dissolved in tetrahydrofuran was poured into a reaction flask containing potassium carbonate. 2,2'-Bisphenol A dissolved in tetrahydrofuran was added dropwise to the reaction flask. The mixture was reacted in an ice bath for 30 minutes, then filtered and rotary evaporated to obtain a crystalline product. Tetrahydrofuran and hexamethylenediamine were added to the reaction vessel and stirred. The crystalline product dissolved in tetrahydrofuran was added dropwise to the reaction vessel and then filtered, washed, and distilled to obtain a flame retardant material. 24 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 2 parts of short-chain fluorinated polymer resin, 8 parts of flame retardant material, and 0.4 parts of lithium chloride were added to a solvent and stirred to obtain a copolymer spinning solution. The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. Nanofiber membranes are bonded to the top and bottom sides of the microporous membrane, and then hot-pressed. A waterproof coating is then sprayed onto the nanofiber membrane to obtain a waterproof and breathable membrane.
[0028] Furthermore, flame-retardant materials containing terminal amino groups of cyclophosphonitrile derivatives synthesized through trichlorophosphazene are encapsulated within copolymer fibers. During combustion of the breathable membrane, the flame-retardant material decomposes at high temperatures to generate phosphorus-containing free radicals and nitrogen-containing gases. In this process, the phosphorus-containing free radicals PO· capture H· and OH· in the combustion chain reaction, thereby interrupting flame propagation. The nitrogen-containing gases NH3 and N2 can dilute the oxygen concentration, thereby inhibiting combustion. In addition, the acidic substances such as phosphoric acid and metaphosphoric acid produced by the decomposition of the flame-retardant material catalyze the dehydration and carbonization of the polyvinylidene fluoride-hexafluoropropylene copolymer within the microporous membrane, forming a dense char layer, which further isolates oxygen and heat transfer. Moreover, the terminal amino groups within the flame-retardant material form hydrogen bonds with the fluorocarbon groups in the polyvinylidene fluoride-hexafluoropropylene molecular chain, enhancing the interfacial bonding force between the char layer and the matrix, improving the stability of the char layer, and enhancing the flame-retardant performance.
[0029] Example 5, please refer to Figure 1 , Figure 5 and Figure 6 A flame-retardant, waterproof, and breathable membrane for building applications, the preparation method of which includes the following steps: Vanillin was dissolved in ethanol and heated to 60°C under a nitrogen atmosphere. 4,4-Diaminodiphenylmethane dissolved in ethanol was added dropwise, followed by the flame retardant diphenyl phosphate, resulting in a mixture. This mixture was then poured into dichloromethane and subjected to ethanol recrystallization, filtration, and washing. The washed product was placed in a vacuum drying oven and dried at 80°C for 24 hours to obtain a vanillin-based flame retardant monomer. Hexamethylene diisocyanate and dibutyltin dilaurate were added to polytetrahydrofuran diol, and the mixture was heated to 70°C under a nitrogen atmosphere to obtain polyurethane. The prepolymer was prepared by dissolving vanillin-based flame retardant monomer in N,N-dimethylacetamide to obtain a vanillin-based flame retardant monomer solution. The vanillin-based flame retardant monomer solution and chain extender 1,4-butanediol were added to the polyurethane prepolymer, followed by the dropwise addition of dibutyltin dilaurate to obtain a reactant. The reactant was poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 24 hours. The product in the mold was then placed in a vacuum drying oven and dried at 70°C for 24 hours to obtain flame-retardant polyurethane. 42 parts of flame-retardant polyurethane and 0.2 parts of lithium chloride were added to a solvent and heated and stirred in a water bath at 60°C for 4 hours to obtain a polyurethane spinning solution. 22 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 1 part of short-chain fluorinated polymer resin, 6 parts of flame retardant material and 0.2 parts of lithium chloride were poured into a solvent and stirred to obtain copolymer spinning solution; The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. Nanofiber membranes are bonded to the top and bottom sides of the microporous membrane, and then hot-pressed. A waterproof coating is then sprayed onto the nanofiber membrane to obtain a waterproof and breathable membrane.
[0030] Furthermore, diphenyl phosphate binds to polyurethane segments via ester groups, decomposing during combustion to generate phosphoric acid, which catalyzes the dehydration and carbonization of polyurethane, forming a dense char layer that inhibits combustion. The phosphorus-based free radicals released by the flame-retardant polyurethane combine with hydrogen fluoride gas produced by the decomposition of polyvinylidene fluoride-hexafluoropropylene to form phosphate glassy substances, capturing active free radicals in the combustion chain reaction, thereby further inhibiting combustion. The dehydration and carbonization of polyurethane forms a dense char layer, while the benzene ring structure of vanillin generates a graphitized char layer. The two layers stack together to form a heat and oxygen barrier, further preventing the transfer of heat and oxygen. Moreover, the vanillin-based flame-retardant diol is embedded in the polyurethane main chain through chemical bonds, avoiding the migration problems of traditional flame retardants and achieving long-lasting flame retardancy.
[0031] Example 6, please refer to Figure 1 and Figure 7 A flame-retardant, waterproof, and breathable membrane for building applications, the preparation method of which includes the following steps: 40 parts of flame-retardant polyurethane and 0.2 parts of lithium chloride were added to a solvent and heated and stirred in a water bath at 60 °C for 4 hours to obtain a polyurethane spinning solution. 20 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 1 part of short-chain fluorinated polymer resin, 5 parts of flame retardant material and 0.2 parts of lithium chloride were poured into a solvent and stirred to obtain copolymer spinning solution; The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. End-capsulated silicone oil and isopropanol were sequentially added to a reaction vessel and stirred. A silane coupling agent was added dropwise, followed by tetraethyl orthosilicate and octyltriethoxysilane. The mixture was stirred for 0.5 hours, and then deionized water was added dropwise to obtain the pre-product. The self-healing microcapsules were blended with the pre-product to obtain a waterproof coating material. Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed and stirred until homogeneous to obtain a silanol solution. Gum arabic powder was added to deionized water, along with epoxy resin, monohydroxy polydimethylsiloxane, and dimethyl methylphosphonate. The mixture underwent emulsification to obtain an emulsion. The silanol solution was added dropwise to the emulsion, and the pH was adjusted to 9 with ammonia. The mixture was then reacted in a 50°C water bath for 6 hours to obtain silicone gel shell microcapsules. The silicone gel shell microcapsules were then added to a copper chloride solution, followed by a tannic acid solution. The reaction was carried out in a water bath at ℃ for 24 hours, followed by filtration and washing to obtain self-healing microcapsules. Nanofiber membranes were then attached to the upper and lower sides of the microporous membrane, and hot-pressed. A waterproof coating was then sprayed onto the nanofiber membrane to obtain a waterproof and breathable membrane.
[0032] Furthermore, when the breathable membrane develops microcracks due to mechanical damage or environmental stress, the self-healing microcapsules in the waterproof coating rupture due to stress concentration, releasing repair agents, such as epoxy components. These repair agents penetrate the cracks through capillary action, forming new chemical bonds with the coating to achieve in-situ repair of the cracks. While repairing the cracks, the microcapsule repair agent anchors the flame-retardant component, dimethyl methylphosphonate, within the microcapsules to the repaired area through a cross-linking reaction. This maintains the continuity of the flame-retardant char layer during the combustion of the breathable membrane, preventing the flame from spreading along the cracks. The flame-retardant component, dimethyl methylphosphonate, encapsulated in the self-healing microcapsules, is directionally delivered to the damaged area during the repair process. This allows the flame-retardant component to form a synergistic effect with the phosphorus-nitrogen flame-retardant system in the flame-retardant polyurethane matrix within the microporous membrane during combustion, inhibiting combustion.
[0033] Comparative Example 1: A flame-retardant, waterproof, and breathable membrane for construction, the preparation method of which includes the following steps: 60 parts of flame-retardant polyurethane and 1 part of lithium chloride were added to a solvent and heated and stirred in a water bath at 60 °C for 4 hours to obtain a polyurethane spinning solution. 30 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 5 parts of short-chain fluorinated polymer resin, 15 parts of flame retardant material and 1 part of lithium chloride were poured into a solvent and stirred to obtain copolymer spinning solution. The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. Nanofiber membranes are bonded to the top and bottom sides of the microporous membrane and then subjected to hot pressing to obtain a waterproof and breathable membrane.
[0034] Example 1, please refer to Figure 1 and Figure 8 A flame-retardant, waterproof, and breathable membrane for building applications, the preparation method of which includes the following steps: 60 parts of flame-retardant polyurethane and 1 part of lithium chloride were added to a solvent and heated and stirred in a water bath at 60 °C for 4 hours to obtain a polyurethane spinning solution. 30 parts of polyvinylidene fluoride-hexafluoropropylene copolymer, 5 parts of short-chain fluorinated polymer resin, 15 parts of flame retardant material and 1 part of lithium chloride were poured into a solvent and stirred to obtain copolymer spinning solution. The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of a multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. A waterproof and breathable membrane is obtained by spraying a waterproof coating on both the top and bottom sides of the microporous membrane.
[0035] Performance testing Test 1 Tensile property test: The breathable membranes prepared in Examples 1-6 and Comparative Examples 1-2 were cut into 50mm×300mm samples and tested according to the method of national standard GB / T1040-2006. The samples were clamped in the fixture of the universal testing machine and stretched until the sample broke. The data were recorded. Test 2 Hydrophobicity test: The breathable membranes prepared in Examples 1-6 and Comparative Examples 1-2 were tested according to the national standard GB / T4851-2014. The surface wettability was tested using an optical contact angle tester. The volume of the water droplet selected for the test was 5 µL, and the test contact angle was recorded. Test 3: Moisture permeability test: The breathable membranes prepared in Examples 1-6 and Comparative Examples 1-2 were tested using a moisture permeability tester according to GB / T12704. The breathable membrane was placed on a moisture permeation cup containing 34 mL of deionized water, and the moisture permeation cup was placed in the moisture permeation tester for 1 hour to balance before being removed and the moisture permeation amount was calculated.
[0036] Test 4 Limiting Oxygen Index Test: The breathable membranes prepared in Examples 1-6 and Comparative Examples 1-2 were cut into 150mm×50mm samples, one end of which was fixed in the combustion column. The top of the sample was ignited with an igniter, and the lowest oxygen concentration required for the sample to burn for 2 minutes was recorded as the oxygen index.
[0037] Table 1 Test results of sample performance testing Example 1 32 137.64 672 31.4 Example 2 28 134.73 753 29.5 Example 3 25 130.28 872 28.7 Example 4 22 127.23 943 27.5 Example 5 19 122.91 1095 26.3 Example 6 17 121.15 1143 25.8 Comparative Example 1 29 132.41 835 27.9 Comparative Example 2 23 133.15 872 27.4 Working principle: Through the interpenetrating network structure of polyurethane and polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution, two types of nanofibers work synergistically to achieve high air permeability, imparting hydrophobicity to the microporous membrane and preventing liquid water penetration. The nanofiber membrane is bonded to the surface of the microporous membrane, so that the nanoscale pores of the nanofiber membrane and the microscale pores of the microporous membrane complement each other. This blocks water droplet penetration without affecting the permeation of water vapor, thereby further enhancing the waterproof performance of the breathable membrane. Octyl long-chain alkyl groups are anchored to the coating surface through hydrolysis, forming a low surface energy structure, which makes the coating hydrophobic and enhances the waterproof performance of the breathable membrane. Phosphoric acid and metaphosphoric acid produced by the decomposition of flame retardant materials catalyze the dehydration and carbonization of polyvinylidene fluoride-hexafluoropropylene copolymer in the microporous membrane, forming a dense carbon layer and improving the flame retardant performance.
[0038] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
Claims
1. A flame-retardant, waterproof, and breathable membrane for use in construction, characterized in that: The microporous membrane comprises, by weight, the following components: 40-60 parts flame-retardant polyurethane, 5-15 parts flame-retardant material, 20-30 parts polyvinylidene fluoride-hexafluoropropylene copolymer, 0.4-2 parts lithium chloride, and 1-5 parts short-chain fluorinated polymer resin. The preparation method of the microporous membrane includes the following steps: (1) Add flame-retardant polyurethane and half of lithium chloride to the solvent, heat and stir in a water bath at 60 °C for 4 h to obtain polyurethane spinning solution; (2) Pour the polyvinylidene fluoride-hexafluoropropylene copolymer, short-chain fluorinated polymer resin, flame retardant material and the remaining lithium chloride into a solvent and stir to obtain copolymer spinning solution; (3) The polyurethane spinning solution and the copolymer spinning solution were respectively loaded into the syringes of the multi-needle electrospinning machine. The syringes containing the polyurethane spinning solution and the copolymer spinning solution were arranged alternately. A voltage of 50kV and a feed speed of 3mL / h were applied to perform electrospinning to obtain a microporous membrane. The microporous membrane has nanofiber membranes attached to both sides. The preparation method of the nanofiber membrane includes the following steps: Lithium chloride was added to a mixture of tetrahydrofuran and N,N-dimethylformamide, along with aminestyrene-butadiene-styrene block copolymer and hydrogen-containing silicone oil. The mixture was stirred to obtain a mixed spinning solution. The mixed spinning solution was then propelled through the syringe of a multi-needle electrospinning machine to spin nanofiber membranes. A waterproof coating is sprayed onto the nanofiber membrane, and the method for preparing the waterproof coating includes the following steps: End-capsulated silicone oil and isopropanol were poured into a reaction vessel in sequence and stirred. Silane coupling agent was added dropwise, followed by tetraethyl orthosilicate and octyltriethoxysilane. The mixture was stirred for 0.5 h, and deionized water was added dropwise to obtain the pre-product. The self-healing microcapsules were then blended with the pre-product to obtain a waterproof coating material. The method for preparing the self-healing microcapsules includes the following steps: Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed and stirred until homogeneous to obtain a silanol solution. Gum arabic powder was poured into deionized water, and epoxy resin, monohydroxy polydimethylsiloxane, and dimethyl methylphosphonate were added. The mixture underwent emulsification to obtain an emulsion. The silanol solution was added dropwise to the emulsion, and the pH was adjusted to 9 with ammonia. The mixture was reacted in a 50°C water bath for 6 hours to obtain silicone gel shell microcapsules. The silicone gel shell microcapsules were poured into a copper chloride solution, and tannic acid solution was added. The mixture was reacted in a 50°C water bath for 24 hours. After filtration and washing, self-healing microcapsules were obtained. The solvent is selected from N,N-dimethylformamide and N,N-dimethylacetamide. The microporous membrane and the nanofiber membrane are bonded together by hot pressing.
2. The flame-retardant, waterproof, and breathable membrane for building applications according to claim 1, characterized in that: The preparation method of the flame-retardant material includes the following steps: The trichlorophosphazene dissolved in tetrahydrofuran was poured into a reaction flask containing potassium carbonate. 2,2'-biphenyl hydroquinone dissolved in tetrahydrofuran was added dropwise to the reaction flask. The mixture was reacted in an ice bath for 30 minutes. The mixture was then filtered and rotary evaporated to obtain the crystalline product. Tetrahydrofuran and hexamethylenediamine are added to a reaction vessel and stirred. The crystalline product dissolved in tetrahydrofuran is then added dropwise to the reaction vessel, followed by filtration, washing, and distillation to obtain a flame-retardant material.
3. The flame-retardant, waterproof, and breathable membrane for construction according to claim 1, characterized in that: The flame-retardant polyurethane is a vanillin-based flame-retardant polyurethane, and the preparation method of the vanillin-based flame-retardant polyurethane includes the following steps: Hexamethylene diisocyanate and dibutyltin dilaurate were added to polytetrahydrofuran diol and heated to 70°C under a nitrogen atmosphere to obtain a polyurethane prepolymer. The vanillin-based flame retardant monomer was dissolved in N,N-dimethylacetamide to obtain a solution of the vanillin-based flame retardant monomer. The vanillin-based flame retardant monomer solution and chain extender 1,4-butanediol were added to the polyurethane prepolymer, and dibutyltin dilaurate was added dropwise to obtain the reactants. The reactants were poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 24 hours. The product in the mold was then placed in a vacuum drying oven and dried at 70°C for 24 hours to obtain vanillin-based flame-retardant polyurethane.
4. The flame-retardant, waterproof, and breathable membrane for building applications according to claim 3, characterized in that: The preparation method of the vanillin-based flame retardant monomer includes the following steps: Vanillin was dissolved in ethanol, heated to 60°C under a nitrogen atmosphere, and 4,4-diaminodiphenylmethane dissolved in ethanol was added dropwise. Then, flame retardant diphenyl phosphate was added to obtain a mixture. The mixture was poured into dichloromethane, recrystallized from ethanol, filtered and washed, and the washed product was placed in a vacuum drying oven and dried at 80°C for 24 hours to obtain vanillin-based flame retardant monomer.
5. A flame-retardant method for a flame-retardant, waterproof, and breathable membrane used in construction, applicable to the flame-retardant, waterproof, and breathable membrane used in construction as described in any one of claims 1-4, characterized in that: The flame-retardant method includes the following steps: S1. When the waterproof and breathable membrane burns, the microporous membrane in the waterproof and breathable membrane forms a dense char layer, which acts as a flame retardant.
6. A flame-retardant method for a flame-retardant, waterproof, and breathable membrane used in construction according to claim 5, characterized in that: The flame-retardant method further includes the following steps: When the S11 waterproof and breathable membrane is damaged by fire, the self-healing microcapsules rupture and release dimethyl methylphosphonate, forming a local flame-retardant barrier.
Citation Information
Patent Citations
An ultra-thin, highly flame-retardant, breathable, and waterproof membrane and its preparation method
CN106827687B
Highly-waterproof highly-breathable nanofiber membrane and preparation method thereof
CN110258021A